Gamification: A Sharing and Storing Information Model at the Malaysian Institute of Teacher Education - Rahman, M.N.A.; Awang, W.M.K.W.; Hanafiah, S.H.M.; Amin, M.Z.M. (2020)
Gamification is a new technique utilising game mechanisms or elements in nongaming contexts for commercial or educational purposes. While gamification seems to be easy to use in a variety of daily activities, challenges will arise when online digitizing processes are created and combined with educational apps. Therefore, this article describes the concept of online gamutation for the purpose of storing and sharing information. The online model is designed to involve all members of the Teacher Education Institute (IPG) and the public to form a group in the collection and dissemination of academic knowledge. The information management process at the Teacher Education Institute (IPG) is often found to be problematic because there is no systematic information storage system. Lecturers and students at IPG mostly keep their teaching and learning materials individually. This situation results in the loss of information resources and difficulty in recovering and also tracing information when needed. To solve the problem, the "Information Sharing for Learning" (iSL) model was developed to manage teaching and learning resources at IPG. This model is expected to motivate and encourage users to use this application and will further increase the amount of collection of stored information sources.